Pneumatology and the Christian-Buddhist dialogue : does the Spirit blow through the middle way? - Yong, Amos (Studies in systematic theology (Leiden, Netherlands), 2012)
This project at the interface of Buddhist-Christian studies, comparative theology, and Christian systematic theology proceeds by way of exploring questions related to the presence and activity of the Holy Spirit in a 21st century world of many faiths.